Co-Creation Innovation: Peran Konsumen Sebagai Mitra dalam Design Thinking - Daniel Daniel; Arjuna Arjuna; Tien Suharti; Oktavianus Oktavianus; Megawaty Megawaty (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study analyzes the role of consumers as innovation partners in the co-creation innovation approach through the implementation of design thinking. The method used is a Systematic Literature Review guided by PRISMA, involving articles obtained from Google Scholar, Scopus, ScienceDirect, Springer, and Emerald Publishing from 2010 to 2024. Of the 40 articles identified, 20 were selected as the main sources. The findings show that co-creation innovation strengthens the effectiveness of design thinking through consumer involvement in the stages of empathize, define, ideate, prototype, and test. Consumers act as sources of ideas, development participants, solution testers, and innovation evaluators. This approach enhances innovation relevance, consumer engagement, customer loyalty, and co-learning processes. However, its implementation still faces challenges, including variations in consumer participation, multi-stakeholder coordination, limited resources, and the suboptimal use of digital technology. This study contributes to integrating the concepts of co-creation innovation, consumer engagement, value co-creation, and design thinking into a systematic review.